2011
DOI: 10.1143/jpsj.80.034706
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Dynamical Coherent-Potential Approximation Approach to the Ferromagnetism of Fe, Co, and Ni

Abstract: Magnetic properties of Fe, Co, and Ni at finite temperatures have been investigated on the basis of the first-principles dynamical CPA (Coherent Potential Approximation) combined with the LDA (Local Density Approximation) + U Hamiltonian in the Tight-Binding Linear Muffintin Orbital (TB-LMTO) representation. The Hamiltonian includes the transverse spin fluctuation terms. Numerical calculations have been performed within the harmonic approximation with 4th-order dynamical corrections. Calculated single-particle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 80 publications
(107 reference statements)
1
19
0
2
Order By: Relevance
“…For the temperature trend, Igoshev et al found a weak decrease of bcc-Fe effective moments with temperature [14]. Kakehashi and Patoary found a weak increase in effective moment with temperature in their dynamical CPA calculations for bcc Fe [16]. Leonov et al [5] used GGA+DMFT and calculated the temperature dependence of the square of the instantaneous local moments m 2 z .…”
Section: A Average Local Magnetic Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the temperature trend, Igoshev et al found a weak decrease of bcc-Fe effective moments with temperature [14]. Kakehashi and Patoary found a weak increase in effective moment with temperature in their dynamical CPA calculations for bcc Fe [16]. Leonov et al [5] used GGA+DMFT and calculated the temperature dependence of the square of the instantaneous local moments m 2 z .…”
Section: A Average Local Magnetic Momentsmentioning
confidence: 99%
“…With the advent of high performance computational resources, advanced first-principles techniques can now be applied to study the magnetic and electronic structure of Fe at elevated temperature. These include the dynamical mean field theory (DMFT) [5,[8][9][10][11][12][13][14], Hubbard models [15], the dynamical coherent potential approximation [16], extended Heisenberg models based on parameters calculated with density functional theory [17][18][19][20][21], spin cluster expansions [22][23][24], or spin-fluctuation theory [6]. For an overview of the recent advances in this field see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of external stress on the electron density and the gradient distribution of the system are considered in the GGA function. So the more accurate calculation can be obtained by the selection of GGA function [19].…”
Section: Simulation Of the Process Of Stress-magnetism Couplingmentioning
confidence: 99%
“…The dynamic theories based on the local approximation [4,5] do not allow to estimate the SRO quantitatively.…”
Section: Introductionmentioning
confidence: 99%